STRATEGIES IN OVERCOMING SPEAKING ANXIETY IN A VIRTUAL CLASSROOM PRESENTATION: A DESCRIPTIVE QUALITATIVE STUDY AT ONE VOCATIONAL SCHOOL - Ridha Mardiani; Apriyani (English Education Department of STKIP Pasundan, 2021)
The purpose of this research is to investigate the factors that caused speaking anxiety in a virtual classroom presentation and the strategies to overcome it. The research setting is in one vocational high school in Cimahi, West Java, Indonesia in which ten second grade students majoring in fashion design class (Tata Busana) were selected to be participants of the study. The study employed descriptive qualitative design where the data obtained in a mixed way through observation, modified FLCAS questionnaire and interview. Due to the pandemic situation, classroom observations were carried out in the virtual classroom. Then the data were analyzed in accordance with the theme called coding and categorizing. The findings showed that the factors caused students’ speaking anxiety in delivering virtual classroom presentation are: personal and interpersonal anxiety, learner beliefs about language learning, lack of preparation and fear of making mistakes. The researchers also found some students’ strategies to overcome their speaking anxiety which are greatly helped them lessen their speaking anxiety. Those are: relaxation and resignation, preparation, peer seeking, and positive thinking. The findings of this research provide suggestions for teachers to improve their creativity in teaching process to create a friendly classroom environment to overcome students’ anxiety in classroom presentation.